Database and XML Technologies 4th International XML Database Symposium, XSym 2006, Seoul, Korea, September 10-11, 2006, Proceedings - Amer-Yahia, Sihem; Bellahsène, Zohra; Hunt, Ela; Unland, Rainer; Yu, Jeffrey Xu (Information Systems and Applications, incl. Internet/Web, and HCI, 2006)
The theme of the XML Database Symposium (XSym) is the convergence of database technology with XML technology. Since the first International XML Symposium in 2003, XSym has continued to provide a forum for academics, practitioners, users and vendors to discuss the use of and synergy between advanced XML technologies. XSym 2006 received 32 full paper submissions. Each submitted paper underwent a rigorous review by independent referees. These proceedings represent a collection of eight excellent research papers. Their focus is on building XML repositories and covers the following topics: XML query processing, caching, indexing and navigation support, structural matching, temporal XML, and XML updates. The organizers would like to express their gratitude to the XSym program c- mittee for their efforts in providing very thorough evaluations of the submitted papers under significant time constraints. We also would like to thank Microsoft for their sponsorship and for the use of the Microsoft Conference Management Toolkit, and the local organizers, especially, Kyuseok Shim, for all they did to make XSym a pleasant and successful event. July 2006 Sihem Amer-Yahia Zohra Bellahsene Jeffrey Xu Yu Ela Hunt Rainer Unland.